Dielectric-Backed Aperture Resonators for X-Band in vivo EPR Nail Dosimetry - Grinberg, Oleg (Radiat Prot Dosimetry, 2016)
A new resonator for X-band in vivo EPR nail dosimetry, the dielectric-backed aperture resonator (DAR), is developed based on rectangular TE(102) geometry. This novel geometry for surface spectroscopy improves at least a factor of 20 compared to a traditional non-backed aperture resonator. Such an increase in EPR sensitivity is achieved by using a non-resonant dielectric slab, placed on the aperture inside the cavity. The dielectric slab provides an increased magnetic field at the aperture and sample, while minimizing sensitive aperture resonance conditions. This work also introduces a DAR semi-spherical (SS)-TE(011) geometry. The SS-TE(011) geometry is attractive due to having twice the incident magnetic field at the aperture for a fixed input power. It has been shown that DAR provides sufficient sensitivity to make biologically relevant measurements both in vitro and in vivo. Although in vivo tests have shown some effects of physiological motions that suggest the necessity of a more robust finger holder, equivalent dosimetry sensitivity of approximately 1.4 Gy has been demonstrated.